Managing Power: The Practical Work of Negotiating Interests - Christie Knittel Mabry; Arthur L. Wilson (Adult Education Research Conference, 2001)
The purpose of this study was to investigate how adult educators negotiate power and interests in program planning for training and development in a corporate setting. The research methodology was a descriptive qualitative study of typical program planning practices of adult educators in a multi-national corporation. The chief finding was that planners' "practical" strategic action for negotiating interests and power varied according to specific situations and how planners perceived the involvement of various stakeholders.